Differences in the Behavior of Dental Caries Prevention: Puzzles and Story Telling as a Media for Health Education - Damayanti, Gita Retno; Hidayat, A Aziz Alimul; Marini, Gita; Setijowati, Nanik (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2016)
Background: Dental caries is a preventable disease. This prevention covers all aspects of dentistry carried out by dentists, individuals, and society that affect the health of the oral cavity. Prevention services are focused on the early stages, before the onset of disease or pre-pathogenesis. At the onset stage, the disease is a primary preventive service or a service to prevent disease. This is marked by efforts to improve health (Health Promotion) and provide special protection (specific protection).Objective: To explore the differences in dental caries prevention behavior: puzzles and storytelling as a medium for health education.Methods: Quasi-experimental design research with non-equivalent control group design.Results: Prevention of dental caries in the group that was given health education by means of a puzzle game showed an average of adequate prevention behavior (20.9); with storytelling games, it shows the average of good preventive behavior (26.5); The prevention of dental caries in the control group showed an average of adequate prevention behavior (12.8), and differences in behavior between groups given puzzle games and storytelling in the prevention of dental caries in children at Pacarkembang Kindergarten Surabaya with the result ρ = 0.000.Conclusion: There is an influence between health education with puzzle games and storytelling in the prevention of dental caries in children.